Online Assessment of Motor, Cognitive, and Communicative Achievements in 4-Month-Old Infants - Corinna Gasparini; Barbara Caravale; Valentina Focaroli; Melania Paoletti; Giulia Pecora; Francesca Bellagamba; Flavia Chiarotti; Serena Gastaldi; Elsa Addessi (MDPI AG, 2022)
Remote methods for data collection allow us to quickly collect large amounts of data, offering several advantages as compared to in-lab administration. We investigated the applicability of an online assessment of motor, cognitive, and communicative development in 4-month-old infants based on several items of the Bayley Scales of Infant Development, 3rd edition (BSID-III). We chose a subset of items which were representative of the typical developmental achievements at 4 months of age and that we could administer online with the help of the infant's caregiver using materials which were easily available at home. Results showed that, in a sample of infants tested live (N = 18), the raw scores of the BSID-III were significantly correlated with the raw scores of a subset of items corresponding to those administered to a sample of infants tested online (N = 53). Moreover, for the "online" participants, the raw scores of the online assessment did not significantly differ from the corresponding scores of the "live" participants. These findings suggest that the online assessment was to some extent comparable to the live administration of the same items, thus representing a viable opportunity to remotely evaluate infant development when in-person assessment is not possible.